Knowledge in Motion: Highly-Skilled Migration and the Role of Regional Networks - David, Alexandra; Coenen, Frans (Advances in Social Sciences Research Journal, 2019)
This study gives insights into the performance of actor networks in the identification of human capital in form of highly-skilled immigrants and the development and implementation of human capital strategies for this target group, esp. The consideration of multiple actor networks as co-creators and co-producers of a regional human capital agenda focussing on highly-skilled immigrants is a contribution to regional human capital development. Hereby, actors’ networks were studied as a regional resource based on regional social capital. Especially actor networks, which are not primarily created for human capital development, such as alumni networks, are here discussed as innovative actors in the development of bottom-up strategies to attract and bind highly-skilled immigrants.